Outcomes and prognostic factors that influence the success of tooth autotransplantation in children and adolescents. Issue 5 (14th July 2017) - Kafourou, Vasiliki; Tong, Huei Jinn; Day, Peter; Houghton, Nadine; Spencer, R. James; Duggal, Monty
Abstract: Background/Aim: Tooth autotransplantation has been advocated for replacement of missing teeth or teeth that are unsuitable for restoration. The aim of this study was to investigate the outcomes and prognostic factors that influenced the success of tooth transplantation in a paediatric population. Materials and Methods: Data were extracted from the records of 75 patients (89 teeth). Demographic and prognostic factors were recorded and analysed for the clinical and radiographic outcomes for periodontal ligament (PDL) and pulp healing of transplanted teeth. Results: The mean age at transplant was 13.2 years, and the mean follow‐up observation period was 2.6±1.8 years with a range of 12.0 months to 9.9 years. The main reason for transplantation was to replace upper central incisors lost or missing due to dental trauma, hypodontia and dilaceration. Of the 45 teeth that were monitored for pulp revascularization, 75.6% showed clinical and radiographic signs of pulp healing and 24.4% showed signs of pulp necrosis and infection. Pulp healing was significantly related to the stage of root development of the transplant. Favourable PDL healing was observed in 87.6% of the transplants, while 13.5% showed signs of replacement resorption. PDL healing was significantly related to the stage of root formation of the transplanted tooth at the time of the surgery, the ease of handling and placement of the tooth, and the status of the alveolar bone at the recipient site at the time of the surgery. Overall success of tooth transplantation was 87.6%, and the survival rate was 94.4%. Conclusions: Tooth transplantation carried out in children and adolescents demonstrated high success and survival, with the stage of root development influencing both the pulp and PDL healing of the transplanted teeth.